2022
DOI: 10.1007/s40670-022-01602-0
|View full text |Cite
|
Sign up to set email alerts
|

Near-Peer Teaching in Conjunction with Flipped Classroom to Teach First-Year Medical Students Basic Surgical Skills

Abstract: Background There is increasing evidence that students are completing medical school with insufficient surgical education. Near-peer tutoring and flipped classroom formatting may be used to enhance learning while simultaneously relieving faculty burden of teaching. Here, we qualitatively evaluate a 3-month course that integrates the use of near-peer teaching and flipped classroom formatting, with the goal of increasing first-year medical students’ self-perceived confidence in performing basic sutur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…These styles of teaching can improve student confidence and learning performance, as shown in previous studies [2]. The novelty of the work by Lu et al [1] is the implementation of both teaching styles in conjunction from an early stage of the student's medical career. This has its merits as shown by Manning et al [3], who found that students who had early and prolonged opportunities to practice a procedural skill in controlled environments had great confidence in patient interactions.…”
Section: Dear Editormentioning
confidence: 75%
See 3 more Smart Citations
“…These styles of teaching can improve student confidence and learning performance, as shown in previous studies [2]. The novelty of the work by Lu et al [1] is the implementation of both teaching styles in conjunction from an early stage of the student's medical career. This has its merits as shown by Manning et al [3], who found that students who had early and prolonged opportunities to practice a procedural skill in controlled environments had great confidence in patient interactions.…”
Section: Dear Editormentioning
confidence: 75%
“…Although both NPT and FC may prove to be useful tools in furthering BSS training, they cannot yet be used instead of surgeon-supported teaching completely. Lu et al [1] demonstrated these styles of learning from students who have previously attended the course and senior residents. Whilst this may be beneficial when teaching BSS, caution needs to be taken when implementing these results for more complex procedures, without expert faculty supervision.…”
Section: Dear Editormentioning
confidence: 98%
See 2 more Smart Citations
“…A combination of peer teaching with flipped classroom could be considered in this case. In fact, recent research in other subjects has started experimenting with the combination of these two learning approaches, and the results have been positive (Chan et al, 2021;Meng et al, 2022;Lu et al, 2022).…”
Section: Students' Perception Of Peer Teachingmentioning
confidence: 99%